«Being a real defender of the Karanogay people… from any oppression». (Materials for the biog-raphy of the Karanogay manager F.I. Kapelgorodsky) - Mikhail A. Volkhonsky; Akhmet A. Yarlykapov; Sergey B. Manyshev (Кавказология)
The article reveals the main stages of the life path of the last Karanogay manager Philip Iosifovich Kapelgorodsky (1882–1938) – a person whose merits in the arrangement of the Nogai steppe at the beginning of the XX century are unfairly forgotten. The little-studied aspects of his activities as an imperial administrator are highlighted with the involvement of archival data and memoirs. Separate episodes from the biography of F.I. Kapelgorodsky, which determined the turns of his life. His significant contribution to the organization of education in the Nogai steppe, the study and description of the culture, customs, way of life of the Nogais is indicated. A brief description and analysis of his activities during the Soviet period is also given. In addition, the track record of F.I. Kapelgorodsky in 1915, extracted from the funds of the Russian State Military Historical Archive, which allows us to clarify some biographical data.